(untitled) (Scottish Archaeological Internet Reports, 2009)
This chapter presents details of physical description, location, extent of erosion, method of access and previous work. There were a total of 13 structures. Most of these were small, oval hollows or depressions in the ground with only faint traces of walling remaining. The largest structure was a rectangular stone building located in the centre of the island. A stone and turf perimeter wall could be followed around the south, south-east and north sides of the island.